2020
DOI: 10.3390/s21010165
|View full text |Cite
|
Sign up to set email alerts
|

Brachialis Pulse Wave Measurements with Ultra-Wide Band and Continuous Wave Radar, Photoplethysmography and Ultrasonic Doppler Sensors

Abstract: The measurement and analysis of the arterial pulse wave provides information about the state of vascular health. When measuring blood pressure according to Riva-Rocci, the systolic and diastolic blood pressure is measured non-invasively with an inflatable pressure cuff on the upper arm. Today’s blood pressure monitors analyze the pulse wave in reference to the rising or falling cuff pressure. With the help of additional pulse wave analysis, one can determine the pulse rate and the heart rate variability. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The VWM monitor consists of a pulse radar sensor, a Microcontroller Unit (MCU), as well as a data analysis and classification unit, as shown in Figure 1 A. The pulse radar sensor serves the purpose of sensing the motion of the A-V fistula vessel wall [ 14 , 15 ]. The operation principle of the pulse radar sensor is described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The VWM monitor consists of a pulse radar sensor, a Microcontroller Unit (MCU), as well as a data analysis and classification unit, as shown in Figure 1 A. The pulse radar sensor serves the purpose of sensing the motion of the A-V fistula vessel wall [ 14 , 15 ]. The operation principle of the pulse radar sensor is described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the antennas on the human arm work in the near field without any mutual coupling between them. The time shift delay via simulation between the distal (first pair of sensors) and proximal (second pair of sensors) transmission coefficient (S21) waveforms of both sensors is used to estimate PTT at different artery thickness-to-radius coefficients in analogy with the conventional methods in finding PTT from the Electrocardiogram (ECG) and photoplethysmography signals [ 4 ] at two different positions.…”
Section: Introductionmentioning
confidence: 99%
“…Several UWB systems for biosensing and biosignal analysis, all performed in an unobtrusive way, are proposed for monitoring a person's presence and/or collecting his/her health-related parameters simultaneously in a home environment [1][2][3]. Using UWB impulse-radar as a sensing device, the authors of [1] showed that it is possible to recognize a person's presence and monitor and collect his/her health-related parameters (such as breathing and coughing rates) simultaneously in a home environment; in addition, they implemented a machine learning technique (k-nearest neighbor) to automatically classify a static posture using UWB radar data.…”
mentioning
confidence: 99%
“…Specifically, the authors included a total of 35 subjects in their study, inducing emotions (with dedicated videos) and collecting UWB impulse-radar data. A first attempt to use UWB for measuring the arterial blood pressure was presented in [3].…”
mentioning
confidence: 99%